Urban Heritage Decline: Conservation Challenges in the Historic Town of Chukai, Terengganu, Malaysia (International Journal of Built Environment and Sustainability, 2025)
Mapping plays a pivotal role in preserving the cultural identity of heritage towns, serving as a systematic approach to documenting and safeguarding historical assets. In smaller towns like Chukai, Malaysia—a coastal port with a rich history—the loss of historical buildings signals physical deterioration and the erosion of cultural heritage and urban characters. This study investigates both the spatial and physical transformation of Chukai’s historical buildings, integrating content-based document analysis, field-based structured observation, and GIS-based spatial mapping using QGIS software. The research utilises two core spatial datasets from 1995 and 2021, which are cross-referenced with field-verified building conditions and GPS-based location data. Findings reveal significant gaps in conservation strategies and inconsistencies in mapping practices, contributing to the neglect of heritage assets and diminishing the town’s historical identity. Through comparative spatial analysis, the study identifies areas of concentrated heritage loss, particularly along the waterfront, suggesting patterns linked to commercial redevelopment pressures. The study highlights how spatial trends in building loss reflect broader urban policy shortcomings and limited on-ground conservation efforts. This research advocates for an inclusive and strategic approach to heritage preservation by addressing the unique challenges of smaller heritage towns. It underscores the value of integrating mapping technologies into heritage management systems and recommends embedding GIS-based monitoring within local planning frameworks. These insights inspire stakeholders to recognise the value of smaller heritage towns and prioritise their protection within broader cultural and urban sustainability frameworks.
Keywords: Heritage City, Historical Buildings, GIS Mapping, Urban Morphology